Neoliberalism and class tourism in The Darjeeling Limited. Issue 3 (3rd July 2019) - Vermeulen, Timotheus
ABSTRACT: This essay considers Wes Anderson's The Darjeeling Limited (2007) in the context of, and ultimately as an expression of, neoliberalism, the late capitalist ideology defined by a belief in free trade, private property rights, and the homo economicus to the extent that the entirety of our everyday life is financialized. The essay is interested specifically in detailing the formal manner in which the film negotiates the marketization of social relations and the commodification of modes of subjectivity including class identity. Taking into account genre, tone, setting, mise-en-scène, performance and costume, it argues that the film simultaneously critiques and affirms neoliberalism – indeed, it suggests that the former always already implies the latter.